Comparison of Magnetospheric Multiscale ion jet signatures with predicted reconnection site locations at the magnetopause - S. M. Petrinec; J. L. Burch; S. A. Fuselier; R. G. Gomez; W. Lewis; K. J. Trattner; R. Ergun; B. Mauk; C. J. Pollock; C. Schiff; R. J. Strangeway; C. T. Russell; et al. (Geophysical Research Letters)
Abstract Magnetic reconnection at the Earth's magnetopause is the primary process by which solar wind plasma and energy gains access to the magnetosphere. One indication that magnetic reconnection is occurring is the observation of accelerated plasma as a jet tangential to the magnetopause. The direction of ion jets along the magnetopause surface as observed by the Fast Plasma Instrument (FPI) and the Hot Plasma Composition Analyzer (HPCA) instrument on board the recently launched Magnetospheric Multiscale (MMS) set of spacecraft is examined. For those cases where ion jets are clearly discerned, the direction of origin compares well statistically with the predicted location of magnetic reconnection using convected solar wind observations in conjunction with the Maximum Magnetic Shear model.